BK 2108 - the calculation of the normalized relative lumbar disc height: expert approach in the standardized assessment of chondrosis - Schwarze, Martin; Schiltenwolf, Marcus (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
The assessment of the medical conditions (liability-compliant causality) of the BK 2108 is a frequent assessment, which poses a challenge to the medical expert in orthopaedics and trauma surgery. In assessing the load-consistent damage pattern, defined changes in the intervertebral discs as well as the adjacent vertebral bodies must be comprehended in a standardised manner. Of several technical measuring methods, three practicable methods are discussed and their application explained. Thus, methods are provided which allow the medical expert to calculate the normalised relative disc height. In this way, the specifications of the consensus recommendations can be met in order to define the damage profile.